2011
DOI: 10.1007/s12012-011-9138-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Clues in the Protective Effect of Ellagic Acid Against Apoptosis and Decreased Mitochondrial Respiratory Enzyme Activities in Myocardial Infarcted Rats

Abstract: Our previous study described the cardioprotective effects of ellagic acid in an isoproterenol-induced myocardial infarction model. In this study, we are reporting the mechanism of protective action of ellagic acid with respect to apoptosis and mitochondrial respiratory enzymes. Ellagic acid (7.5 and 15 mg/kg) was administered orally as a pretreatment for 10 days. Then, isoproterenol (100 mg/kg) was injected subcutaneously to rats at an interval of 24 h for 2 days. Myocardial infarction was quantified by planim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 37 publications
2
17
1
Order By: Relevance
“…Here, rosuvastatin reduced cardiomyocyte apoptosis by Bax downregulation and mild Bcl-2 upregulation. On the other hand, pretreatment with ellagic acid was unable to significantly protect the cardiomyocytes from apoptosis which contrasts with a report of anti-apoptotic effect of ellagic acid on rats with MI (Mari Kannan and Darlin Quine, 2012). In such report, ellagic acid was administered in smaller doses (7.5 & 15 mg/kg/day) for a shorter period (10 days), which could account for the disagreement with our study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Here, rosuvastatin reduced cardiomyocyte apoptosis by Bax downregulation and mild Bcl-2 upregulation. On the other hand, pretreatment with ellagic acid was unable to significantly protect the cardiomyocytes from apoptosis which contrasts with a report of anti-apoptotic effect of ellagic acid on rats with MI (Mari Kannan and Darlin Quine, 2012). In such report, ellagic acid was administered in smaller doses (7.5 & 15 mg/kg/day) for a shorter period (10 days), which could account for the disagreement with our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Rosuvastatin has been reported to prevent MI induced experimentally by occlusion of left coronary artery in rats (Dourado et al, 2011). Ellagic acid is a polyphenolic compound that is found in strawberries, pomegranates and grapes (Mari Kannan and Darlin Quine, 2012). It possesses a number of biological activities such as antioxidant, antihyperlipidemic, anti-inflammatory and hepatoprotective effects (Rogerio et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, we evaluated the 595 molecular mechanism of vanillic acid on Fas-receptor and caspase 596 mediated apoptosis-signaling pathway in ISO induced myocardial 597 infarcted rats. 598 Previous studies have revealed that oxidative stress causes car-599 diomyocyte apoptosis in ISO induced myocardial infarcted rats 600 [24]. As reported earlier [24], we also observed increased expres- …”
supporting
confidence: 77%
“…598 Previous studies have revealed that oxidative stress causes car-599 diomyocyte apoptosis in ISO induced myocardial infarcted rats 600 [24]. As reported earlier [24], we also observed increased expres- …”
supporting
confidence: 77%
“…The rat sense and anti-sense primers were used. GAPDH: 5′ TTC TTG TGC AGT GCC AGC CTC GTC-3′ and 5′ TAG GAA CAC GGA AGG CCA TGC CAG-3′; Bax: TTC ATC CAG GAT CGA GCA GA and GCA AAG TAG AAG GCA ACG; Bcl-2: CTG GTG GAC AAC ATC GCT CTG and GGT CTG CTG ACC TCA CTT GTG (Kannan & Quine, 2011b). The reverse transcription polymerase chain reaction products were electrophoresed on a 1% agarose gel and visualized by staining with ethidium bromide.…”
Section: Ribonucleic Acid Isolation and Reverse Transcription Polymermentioning
confidence: 99%